Pengaruh Pemahaman Akuntansi Dasar Dan Keaktifan Belajar Terhadap hasil Belajar MYOB Dengan Kemandirian Belajar Sebagai Variabel Moderating - Dimas Fahruzi; Choms Gary Ganda Tua Sibarani; La Hanu; Jufri Darma; Roza Thohiri (Jurnal Pendidikan Akuntansi (JPAK), 2025)
This study aims to significantly test the influence of basic accounting understanding and learning activity on MYOB learning outcomes, with learning independence as a moderating variable. Using a causal associative design, this study attempts to uncover the causal relationship between variables. The research subjects were 62 grade XI AKL students at SMKN 1 Pantai Cermin who had taken the computerized accounting (MYOB) subject, where the entire population was sampled (total sampling). Data were collected through observation, documentation, questionnaires, and tests. The results of the analysis showed several important findings: (1) Basic Accounting Understanding was proven to have a significant influence on MYOB learning outcomes (T-statistic: 3.633; P-value: 0.000). (2) Learning Activity did not show a significant influence on MYOB learning outcomes (T-statistic: 0.916; P-value: 0.181). (3) Learning Independence itself had a significant influence on MYOB learning outcomes (T-statistic: 2.026; P-value: 0.023). (4) The influence of Basic Accounting Understanding on MYOB learning outcomes becomes significant when moderated by learning independence (T-statistic: 1.829; P-value: 0.035). (5) The influence of Learning Activeness on MYOB learning outcomes also becomes significant when moderated by learning independence (T-statistic: 1.724; P-value: 0.042).